Effects of selenium on apoptosis and abnormal amino acid metabolism induced by excess fatty acid in isolated rat hepatocytes. Issue 9 (7th June 2017) - Zhang, Zhigang; Li, Siyu; Jiang, Huijie; Liu, Biying; Lv, Zhanjun; Guo, Changming; Zhang, Haili
Abstract : Potential pharmacological role of Se on excess FFA in rat hepatocytes . In isolated rat hepatocytes, excess cellular FFA induced apoptosis through depleting antioxidant capability and abnormal amino acid metabolism through increasing BCAA abundance. Se protected primary hepatocytes exposed to excess FFA from FFA‐induced apoptosis but not against abnormal amino acid metabolism and insulin resistance. Abstract : Scope: Increased serum free fatty acid (FFA) occurs in subjects with non‐alcoholic fatty liver disease (NAFLD) and also triggers oxidative stress, apoptosis, and insulin resistance. Selenium (Se) is an antioxidant agent. However, the effect of Se on NAFLD or diabetes is still unclear. We investigated the effect of Se on apoptosis and abnormal amino acid metabolism initiated by excess FFA in isolated rat hepatocytes. Methods and results: Primary hepatocytes from rats were isolated and exposed to excessive FFA (0.5 mM oleate/palmitic acid 2:1) and 0.1 μM Se. Se protected primary hepatocytes against oxidative stress and apoptosis induced by excess FFA, but did not play a role on abnormal amino acid metabolism and insulin resistance initiated by FFA in isolated rat hepatocytes. Conclusion: Although Se had the capability of preventing the apoptosis initiated by ROS, insulin resistance failed to be reversed in hepatocytes exposed to FFA. This failure may be attributed to the limitation of Se in regulating branched chain amino acids abundance. This indicates that apoptosis and insulin resistance might be involved in different pathways when isolated hepatocytes were exposed to FFA and Se.